Analisis Pemahaman Konseptual Peserta Didik pada Materi Konsep Mol melalui Model Pembelajaran 5E (Engage, Explore, Explain, Elaborate, Evaluate) - Esril Elen Ranna Qasimah; Tritiyatma Hadinugrahaningsih; Elma Suryani (Jurnal Riset Pendidikan Kimia (JRPK), 2025)
This study aims to determine the description (profile) of students' conceptual understanding of the mole concept material through the 5E learning model (Engage, Explore, Explain, Elaborate, Evaluate This study uses a qualitative method. The research was conducted in the even semester of the 2024/2025 academic year in class X-E2 at SMA Negeri 36 Jakarta, involving 36 students. Data in this study were obtained from observation sheets, interviews, reflective journals, student worksheets, teacher notes, and summative tests of conceptual understanding based on the aspects of conceptual understanding according to Anderson and Krathwohl (2001). The 5E learning model consists of five stages, namely engagement, exploration, explanation, elaboration, and evaluation. The level of understanding possessed by students will be analyzed and grouped into four categories in the level of conceptual understanding adapted from Abraham, et.al (1992), namely understanding, lack of understanding, misconceptions, and not understanding. The results of the analysis of students' conceptual understanding show that most students are in the “understanding” category. The highest percentage for the “understanding” category is in the aspect of giving examples and concluding with a value of 100%. The lowest percentage for the “understanding” category is in the aspect of comparing with a value of 75.00%. So based on these data it can be concluded that the application of the 5E learning model can help students improve concept understanding on the material of the mole concept and increase the activeness of students in learning.